Cervical Cancer Screening Practice and Knowledge Among Hispanic Migrant and Seasonal Farmworkers of Michigan. (July 2013) - Knoff, Jayne S.; Harlow, Siobán D.; Yassine, May; Soliman, Amr S.
Background: High incidence of cervical cancer among Hispanics and low utilization of cervical screening among farmworkers led us to examine Pap test use and knowledge among Hispanic farmworkers in Michigan.Methods: Patients and potential patients of Northwest Michigan Health Services, Inc were surveyed in 2 communities (A and B) about their screening knowledge, attitudes, and practice.Results: In all, 324 farmworkers participated, including 184 seasonal and 125 migrant farmworkers. Among the entire study population, 87.7% women reported receiving a Pap test recently, with no difference between migrant and seasonal farmworkers (88.0% and 87.4%, respectively, P = .088). More women from community B reported a recent Pap (93%) compared with those from community A (83%, P = .01). Only 35% of the participants had knowledge of any cervical cancer risk factors.Discussion: Migrant farmworkers may not experience more difficulty in accessing Pap tests than seasonal farmworkers in Michigan. Knowledge about cervical cancer risk factors is low and needs to be addressed in future educational interventions.